USM IEEE SB BAGS SILVER AT DARREL CHONG STUDENT ACTIVITY AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, November 2015 – Universiti Sains Malaysia (USM) IEEE Student Branch (USM IEEE SB) has achieved another milestone by winning the Silver prize at the 2015 Darrel Chong Student Activity Award recently. This award gives recognition for the activities organised by the IEEE bodies around the world that have meaningful impact to the society.